The Effect of Addition of Bambusa Arundinacea (Retz.) Willd. Fibers to Heat-Cured Acrylic Resin on Impact Strength - Elonianty, Chanita; Agustantina, Titien Hary; nirwana, intan (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: The prevalence of acrylic resin dentures fracture due to accidental drop is relatively high especially when it is being cleaned by patient. The effort to strengthen acrylic resin denture was done by adding Bambusa arundinacea (Retz.) Willd fibers, which was based on previous research. It has been proven that the addition of bamboo fiber to self-cured acrylic resin can increase the tensile strength. It has acceptable tensile properties, relatively low cost, high toughness, and good thermal properties. Purpose: To determine the impact strength of heat-cured acrylic resin after the addition of Bambusa arundinacea (Retz.) Willd. fibers at various lengths and weights. Methods: Bambusa arundinacea (Retz.) Willd. fibers with lengths of 2 mm, 6 mm, 12 mm and weights of 3wt%, 6wt%, 9wt% were added to heat-cured acrylic resin. The impact strength of heat-cured acrylic resin was tested using the Charpy method with mini impact tester KRY type. The test results were calculated using the impact strength formula. The research data were analyzed using one-way anova test and Tukey HSD test. Results: The data analysis showed that there was a significant difference in impact strength of heat-cured acrylic resin after the addition of Bambusa arundinacea (Retz.) Willd fibers. Conclusion: Addition of Bambusa arudinacea (Retz.) Willd. fibers increased the impact strength of heat-cured acrylic resin respective to the increment of length and weight of Bambusa arudinacea (Retz.) Willd. fibers.